PEDAGOGICAL SIGNIFICANCE OF THE ORGANIZATION OF 5 DEVELOPMENTAL CENTERS IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Ganieva Vazira Yusufovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the pedagogical significance of the organization of 5 developmental centers in preschool educational organizations.